Effect of Heat Treatment on Mechanical Behaviour of Fly ash Reinforced Al-Si Composite - A Review. (2018) - Shukla, Anurag; Soni, Sanjay; Rana, R.S.; Singh, Alok
Abstract: In recent years the use of metal matrix composite material increased very rapidly due to their high weight to strength ratio, low density, low thermal expansion coefficient, low maintenance and high temperature resistance. The composites which are reinforced with fly ash particulates attracting considerable interest due to their inherent good mechanical properties and low cost followed by Heat Treatment to achieve desired physical and mechanical properties through modification of their crystalline structure of the materials. This paper provides an extensive literature review on the overall performance of varying the size and wt. percentage of fly ash in fly ash reinforced composites with aluminium alloy. Literatures in each category are reviewed according to the keywords mentioned. The literature review framework in this paper provides a clear overview of the usage of fly ash as a reinforcing agent in different matrices along with its distinctive performances.